1995
DOI: 10.1007/bf00202175
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol disposition in Thai patients during and after treatment of falciparum malaria

Abstract: Investigations in animals have suggested that conjugation of paracetamol may be reduced in malaria. We have measured plasma concentrations and the urinary excretion of paracetamol and its phase II metabolites in eight Thai patients during uncomplicated falciparum malaria and in convalescence, following a 1000 mg single oral dose. The apparent oral clearance (Malaria, 3.6; Convalescence, 3.9; ml.min-1.kg-1), the elimination half-life (Malaria, 3.8; Convalescence, 3.7 h) and apparent volume of distribution (Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…PK–PD analysis in the current study shows a dose-dependent effect of acetaminophen on fever clearance time, whereas acetaminophen concentrations were not associated with parasite clearance rates in these artemisinin-sensitive infections. Studies that evaluated acetaminophen in uncomplicated malaria have not reported serious adverse events or hepatotoxicity attributable to acetaminophen [ 28 , 29 ]. The current study shows that administering the maximum recommended daily dosage of acetaminophen results in a moderate increase in aminotransferases, but no patient met criteria for Hy’s law for hepatotoxicity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…PK–PD analysis in the current study shows a dose-dependent effect of acetaminophen on fever clearance time, whereas acetaminophen concentrations were not associated with parasite clearance rates in these artemisinin-sensitive infections. Studies that evaluated acetaminophen in uncomplicated malaria have not reported serious adverse events or hepatotoxicity attributable to acetaminophen [ 28 , 29 ]. The current study shows that administering the maximum recommended daily dosage of acetaminophen results in a moderate increase in aminotransferases, but no patient met criteria for Hy’s law for hepatotoxicity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adult dose is 1000 mg (or 15 mg/kg) every 6 h (maximum daily dose 4000 mg), given orally or via a nasogastric tube (as powdered tablets or suspension which have generally good bioavailability) (Ismail et al . ; Wilairatana et al . ).…”
Section: Section 10: Management Of Severe Malariamentioning
confidence: 97%
“…The C MAX of paracetamol after intramuscular and oral administration (600 mg) were 11.4 and 8.52 mg/l, respectively. The lower C MAX of oral paracetamol is explained by incomplete absorption and the first-pass metabolism that occurs during absorption before paracetamol enters the systemic circulation, and the slower absorption obscuring distribution from an apparent central compartment [ 9 ]. While the pharmacokinetics of paracetamol in severe falciparum malaria have not been studied, the bioavailability of oral paracetamol may be even lower given the decrease in gastric emptying [ 33 ] and splanchnic blood flow [ 34 ] observed in severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples were processed and stored at −80 °C for further analysis in Bangkok, Thailand. Paracetamol plasma concentrations were quantified using high-performance liquid chromatography, as previously described [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation